2023
DOI: 10.3390/ijms24108908
|View full text |Cite
|
Sign up to set email alerts
|

Dietary (Poly)phenols in Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) remains one of the leading causes of death and disability in young adults worldwide. Despite growing evidence and advances in our knowledge regarding the multifaceted pathophysiology of TBI, the underlying mechanisms, though, are still to be fully elucidated. Whereas initial brain insult involves acute and irreversible primary damage to the brain, the processes of subsequent secondary brain injury progress gradually over months to years, providing a window of opportunity for therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…In addition, it may also be related to dietary polyphenols with antioxidant activity, such as resveratrol [ 54 , 71 ], apocynum venetum polyphenols [ 72 ], etc. These substances had neuroprotective effects on the brain [ 73 ], and played a similar role in glioma, including inducing glioma cell apoptosis [ 74 ], reducing its invasiveness [ 74 ], inhibiting its proliferation through NF-κB pathway [ 72 ], and improving the efficacy of radiotherapy and temozolomide [ 71 ]. In previous studies, we also found that higher dietary resveratrol intake was associated with a reduced risk of glioma, and there was a significant nonlinear dose–response relationship between them [ 75 ], which was very similar to the relationship between resveratrol and other cancers [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it may also be related to dietary polyphenols with antioxidant activity, such as resveratrol [ 54 , 71 ], apocynum venetum polyphenols [ 72 ], etc. These substances had neuroprotective effects on the brain [ 73 ], and played a similar role in glioma, including inducing glioma cell apoptosis [ 74 ], reducing its invasiveness [ 74 ], inhibiting its proliferation through NF-κB pathway [ 72 ], and improving the efficacy of radiotherapy and temozolomide [ 71 ]. In previous studies, we also found that higher dietary resveratrol intake was associated with a reduced risk of glioma, and there was a significant nonlinear dose–response relationship between them [ 75 ], which was very similar to the relationship between resveratrol and other cancers [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, MAO-B mainly metabolizes DA and some less clinically relevant chemicals [91]. In this context, the supplementation of polyphenols to rats after post-fluid percussion injury demonstrated a promising neuroprotective action [92]. Further, research findings have also revealed that a polyphenol-rich diet normalizes brain-derived neurotrophic factor (BDNF) levels and synapsin 1-dependent synaptic plasticity.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Furthermore, the implementation of standardized protocols that broaden the spectrum of analysis is essential. These protocols could include high-throughput strategies to address the chemical complexity of phenols, as allowed by in silico analyses (Carecho et al, 2023).…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%